Comparison and modelling of pegylated or unpegylated G-CSF schedules in CHOP-14 regimen of elderly patients with aggressive B-cell lymphoma. - Zeynalova, S.; Ziepert, M.; Scholz, M.; Schirm, S.; Zwick, C.; Pfreundschuh, M.; Loeffler, M. (Ann Hematol, 2013)
Bi-weekly (R)-CHOP therapy is one of the standard treatmentS for elderly patients with aggressive B-cell lymphoma, but it is only feasible with supportive G-CSF treatment. In the trials of the DSHNHL, either unpegylated G-CSF was given daily over 7 or 10 days or pegylated G-CSF was applied at day 4 of each cycle. These schedules were planned on the basis of simulations of a biomathematical pharmacokinetic/pharmacodynamic model. By analysing the observed data, we investigated whether our model predictions were correct and whether even better schedules can be proposed. We used data on 249 matched patients of two prospective trials, RICOVER-60 and PEGFILGRASTIM. The three G-CSF-schedules showed similar outcomes regarding leukocytopenia, infections and days in hospital, with pegylated G-CSF having slightly but not significantly better scores in all three endpoints. Regarding pegylated G-CSF, the best timing is predicted to be any day between days 4 and 7. With respect to unpegylated G-CSF, the starting day is less important, but it should be continued until the end of each cycle.The three G-CSF-schedules are interchangeable in (R)-CHOP-14 for elderly patients with aggressive B-cell lymphoma. Our model correctly predicts time courses of leukocytes. Further model predictions are presented, which can be tested in subsequent clinical trials.
Keywords: Aged; Aged, 80 and over; Antineoplastic Combined Chemotherapy Protocols/*administration & dosage; Cyclophosphamide/administration & dosage; Doxorubicin/administration & dosage; Drug Administration Schedule; Female; Filgrastim; Granulocyte Colony-Stimulating Factor/*administration & dosage; Hospitalization/trends; Humans; Lymphoma, B-Cell/blood/*drug therapy; Male; Middle Aged; Polyethylene Glycols/*administration & dosage; Prednisone/administration & dosage; Prospective Studies; Recombinant Proteins/administration & dosage; Vincristine/administration & dosage